Challenges and emerging approaches in life cycle assessment of engineered nanomaterials usage in anaerobic bioreactor - Jadhav, Pramod; Bin Khalid, Zaied; Mishra, Puranjan; Zularisam, Abdul Wahid; Mohd Nasrullah, Zulkifli (Elsevier, 2022)
Due to the increasing demand for sustainable energy sources and effective management of the ever-increasing volume of organic waste, anaerobic digestion (AD) has continued to play a crucial role in biogas production in recent years. Biochar (BC) is a highly flexible material manufactured by carbonizing organic resources like biomass and trash in line with circular economy standards and \“tailor-made\” for certain purposes. The capacity of BC as an additive to address various well-established crucial difficulties in AD methods has been extensively studied during the last 10 years. Nevertheless, a comprehensive and credible explanation of the BC-AD link remains elusive. The life cycle analysis (LCA) of the biogas enhancement mechanism would provide a quantitative indicator of its long-term viability. The reported LCA studies of AD processes are analyzed in this chapter, showing that few systematic studies cover the whole process; thus results may be inconclusive. LCA results can be influenced by the heterogeneity of the AD method, reactor structure and conditions, and other influences. The absence of a conventional formation for LCAs utilized to the biogas yield method is a component in the inconsistent LCA results. Other considerations for instance systematic maintenance, transportation, system boundaries, temporal units, allocation preference, and waste disposal must be involved in the LCA plan. Notably, the economic pressure of both upstream and downstream systems should be included in the LCA phase. Inevitably, process design, optimization and modeling, and intensification will be the major future research subjects. This chapter provides a thorough and critical examination of the LCA and its sustainability evaluation for the whole AD procedure, which would be helpful in potential research.